Space and Time in Human Life and its Experience in Art. A Study on the Intellectual Exchange between Martin Heidegger and Eduardo Chillida - Rabe, Ana María (Pensamiento. Revista de Investigación e Información Filosófica, 2017)
Martin Heidegger and Eduardo Chillida held a rich and fertile intellectual exchange in 1968 and 1969, by the time they were preparing the artists’ book Die Kunst und der Raum («The Art and the Space»), which was to contain a text on art and space, written by Heidegger, as well as seven litho-collages and one lithography created by Chillida. The article deals with the similarity that exists between the German philosopher’s and the Spanish-Basque sculptor’s conception of space and time. Both understand space in connection with time as something dynamic, inseparable from life and human experience, which is not simply «given», but has to be looked for and realized. Starting point of this article is a circumstance that has not been investigated up to now: Heidegger read and discussed with Chillida the reflections on space that the latter had written and sent to him in the early 1969 at his request. At the end of the article, Chillida’s reflections used by Heidegger in a German translation, when he was preparing his text on «The Art and the Space», will be published for the first time, as well as a bigger selection of Chillida’s reflections, which the artist could have sent to the philosopher, and finally a page of the notes, which Heidegger took on Chillida.